FEATURES OF IMPLEMENTATION OF THE NEWEST TECHNOLOGIES ON THE INTERNATIONAL MARKET: MARKETING ASPECT - PTASHCHENKO, Olena; KARP Victoriуa (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the presented work is to determine the features of the implementation of the latest technologies, to study the state of the international market where they are implemented. The essence of the marketing aspect in the complex of the development of the latest technologies is also defined and a methodical approach to the formation of effective marketing tools for the promotion of the latest technologies on the international market is proposed. During the research, the following methods were used: analysis and synthesis to determine the features and main elements of the implementation of the latest technologies on the international market, as well as to determine effective marketing tools for the promotion of the latest technologies on the market; inductions and deductions for determining the main characteristics of the latest technologies and determining the role of marketing tools in the complex of promoting the latest technologies on the international market; the graphic method was used to visually display the main results of the study. The main results of the study include the following conclusions, which prove the need for constant monitoring of the international technology market. The field of cutting-edge technology is rapidly evolving, and research in this segment is key to further progress. So let’s note that the latest technologies are aimed at improving the state of the surrounding or internal environment, usually the effect of their implementation has a commercialization or social component. Means of marketing in the international market must be creative and innovative. Searching for new ways of communication and promotion helps to attract the attention of consumers to the newest products on the market. The development of medical technologies, such as telemedicine, mobile medical devices and artificial intelligence for diagnosis and treatment, contributes to the improvement of health care and increases the quality of medical services. Developers are making significant strides toward autonomous vehicles, which could change transportation infrastructure and logistics. Consumers are becoming more educated and demanding about technology, and they are looking for products and services that improve their lifestyles and provide greater convenience. The formation of an effective marketing toolkit, which includes the latest digital marketing tools, helps enterprises to ensure adaptation in the market to changes in the environment and to optimize the complex of marketing and management solutions. A methodical approach to the formation of a set of effective marketing tools for promoting the latest technologies on the international market is proposed, which is based on a set of the latest digital marketing tools and allows optimizing marketing and management decisions regarding the implementation of the latest technologies on the market.